Greenhouse gas mitigation technologies in agriculture: Regional circumstances and interactions determine cost-effectiveness. (1st October 2021) - Fellmann, Thomas; Domínguez, Ignacio Pérez; Witzke, Peter; Weiss, Franz; Hristov, Jordan; Barreiro-Hurle, Jesús; Leip, Adrian; Himics, Mihaly
Abstract: Agriculture, forestry and other land use are important components of a global strategy to limit climate change. Using the example of EU agriculture, this paper examines the potential contribution of technological (i.e. technical and management-based) greenhouse gas mitigation options to climate targets. The quantitative framework presented allows to analyze disparities between marginal abatement cost curves (MACCs) derived from two different commonly used approaches, and between aggregated and regional MACCs. Results highlight the importance of assessing mitigation of agricultural emissions from a multi-dimensional perspective, considering regional heterogeneity of biophysical and economic circumstances and comprising both carbon-dioxide (CO2 ) and non-CO2 emissions. Regarding the ranking of technologies in terms of mitigation potential and costs, the results underline the need to consider technologies in a combined manner, avoiding the simple aggregation of mitigation potentials by individual measures without taking their interactions into account. Focusing only on standalone MACCs can lead to an overestimation of the mitigation potential. Conversely, measures classified as relatively high cost in standalone and aggregated MACCs should not be discarded, as they can still be cost-effective in some regions. The analysis shows that there is no 'one size fits all' rule that could be followed for identifying technologies that should be implemented in all regions. From a policy perspective the results imply that farmers should be granted some flexibility to adopt a set of cost-effective mitigation options that best fits their circumstances. Highlights: This paper explores disparities between technology-specific MACCs in agriculture. Mitigation technologies need to be considered in a combined and regional manner. Interactions between measures affect cost-effectiveness of individual technologies. Standalone approaches may discard options that are cost-effective for some regions. Region-specific flexibility is required to find the most cost-effective technology mix.